Analisis Pendidikan Karyawan, Disiplin Kerja dan Prestasi Kerja Karyawan Terhadap Kualitas Layanan Perbankan pada Bank Sumsel Babel Syariah KCP UIN Raden Fatah Palembang - Apriani, Fitri; Azwari, Peny Cahaya (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2023)
This study aims to determine and analyze employee education, work discipline, and employee work performance on the quality of banking services at Bank Sumsel Babel Syariah KCP Uin Raden Fatah Palembang. The entire population is 80 customers of Bank Sumsel Babel Syariah KCP UIN Raden Fatah Palembang, while the sample used in this study was 50 total respondents, with ages ranging from 20-30 years obtained from filling out questionnaires that had been distributed by researchers and sampling techniques with purposive sampling techniques and the method used in this study was quantitative analysis with multiple linear regression and using SPSS version 26. The results of this study show that the perception of education, work discipline, and employee work performance affect the quality of banking services.